Anais da IV Mostra Acreana de Educação, Ciência, Tecnologia e Inovação - Viver Ciência - 2018 - ., . . (South American Journal of Basic Education, Technical and Technological, 2019)
Anais da IV Mostra Acreana de Educação, Ciência, Tecnologia e Inovação - Viver Ciência - 2018